Acoustic-Mechanical Responses of Intact and Flaw-Contained Rock Deformation under Uniaxial Compression: A Comparison - Gui-Lin Wang; Liang Zhang; Zhen Wang; Jian-Zhi Zhang; Fan Sun; Pei-Yong Qiu (Advances in Civil Engineering)
The study of the mechanical properties and cracking behaviors of jointed rock masses is important in rock engineering projects. In the present study, a series of uniaxial compression experiments were conducted on intact rock, and rock masses with single or double preexisting flaws, and then the strength, deformability, and fracture behavior of samples are investigated. Moreover, photographic monitoring technique and emission monitoring technique are introduced to explore the fracturing mode and the acoustic emission (AE) evolution characteristic of fractured rock during the whole loading process. The obtained results show that the preexisting flaw has a strong influence on the mechanical properties, fracture behavior, and AE characteristic of sandstone specimens. In detail, the stress-strain curves show that no significant stress jump occurs at prepeak and postpeak points for intact sandstone specimens; however, the flaw-contained sandstone specimens exhibit distinct stress jump during the entire loading process. Meanwhile, the strength parameters of the the rock specimen is obviously weakened by the preexisting fissures, and the uniaxial compression strength of rock specimens generally decreases with the increase in the number of preexisting fissure as well as the peak strain and the elastic modulus. The failure modes of intact and flaw-contained sandstone specimens exhibit the splitting failure and the mixed failure modes of shear and tension, respectively. Similarly, the maximum AE counts and AE energy both decrease with the increasing number of preexisting flaw. The present research can enhance the understanding of mechanical properties, cracking behaviors, and failure mechanism of jointed rock mass.